2018
DOI: 10.1177/2158244018803132
|View full text |Cite
|
Sign up to set email alerts
|

What Does It Mean to Be Single in Indonesia? Religiosity, Social Stigma, and Marital Status Among Never-Married Indonesian Adults

Abstract: The increasing number of never-married individuals has become a global phenomenon. Like many Asian countries, the sociocultural standard in Indonesia defines being married as a desirable social achievement, which leaves single adults vulnerable to derogation. Religiosity is also highly valued in Indonesian society, to the extent that those who show religious attributes tend to be positively regarded. This study aims to describe how Indonesian society defines the status and to explore the role of religiosity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 52 publications
4
35
0
13
Order By: Relevance
“…For instance, with their tendency to be happier than other categories of marital status like singles, cohabitating, widowed, and the divorced ones who tend to have lower level of life satisfaction, the married people have been reported to have a high level of life satisfaction as reported by (Diener, Suh, Lucas, & Smith, 1999;Diener, Gohm, Suh, & Oishi, 2000, Ha & Kim, 2013. They are also in line with different studies carried out in Indonesia related to subjective well-being/happiness and marital status which have shown that married individuals are happy compared to unmarried ones Himawan et al, 2017Himawan et al, , 2018, Indonesian married individuals seem to be happier than the single ones (Rosifah et al, 2019). Nonetheless, it is not only the case of Indonesia, but also the same all over the world, as it has been revealed in their different studies related to subjective well-being and marital status (Veenhoven, 2006;Yap et al, 2012;Anusic et al, 2014;Greenstein, 2016;Lucas, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…For instance, with their tendency to be happier than other categories of marital status like singles, cohabitating, widowed, and the divorced ones who tend to have lower level of life satisfaction, the married people have been reported to have a high level of life satisfaction as reported by (Diener, Suh, Lucas, & Smith, 1999;Diener, Gohm, Suh, & Oishi, 2000, Ha & Kim, 2013. They are also in line with different studies carried out in Indonesia related to subjective well-being/happiness and marital status which have shown that married individuals are happy compared to unmarried ones Himawan et al, 2017Himawan et al, , 2018, Indonesian married individuals seem to be happier than the single ones (Rosifah et al, 2019). Nonetheless, it is not only the case of Indonesia, but also the same all over the world, as it has been revealed in their different studies related to subjective well-being and marital status (Veenhoven, 2006;Yap et al, 2012;Anusic et al, 2014;Greenstein, 2016;Lucas, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…This idea implies that marriage is viewed as a religious obligation (Himawan, Bambling and Edirippulige 2018b, Ibrahim and Hassan 2009). The perception will make singles to feel burdened and intimidated especially when they are in their religious community, particularly, when their status is involuntarily single (Himawan, Bambling and Edirippulige 2018b) In this paper, we argue that the persistent universal norms towards marriage and social stigma towards singleness continue to overshadow the effect of increase in educational achievement to singlehood in Indonesia. Following the multiple equilibrium framework by Esping-Andersen (2009) and Esping-Andersen and Billari (2015), Indonesia's gender norm and attitude has shifted from conservative-traditional male-breadwinner model to a more egalitarian context, but the adaptation of women in the labour market role and men in domestic sphere is still slowly progressing.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Religion also plays a significant role in shaping the norms towards permanent singlehood. As one of the largest Moslem countries in the world, most of Indonesian society interpret marriage as one of God's demands (Himawan, Bambling and Edirippulige 2018b). This idea implies that marriage is viewed as a religious obligation (Himawan, Bambling and Edirippulige 2018b, Ibrahim and Hassan 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Private law is a law that only regulates the relationship between the diversity of the state or society itself, such as maturity, marriage, divorce, immortality, inheritance, property, business activities, and actions of nature. Civil or private, not public, is different from criminal law or public law which regulates matters related to the state and public interests such as politics, elections, crime, and others [6] [12][13] [14]. As for the systematics of civil law in Indonesia, there are two opinions, that are:…”
Section: 1mentioning
confidence: 99%
“…Based on article 180 paragraph (1) of the HIR stated "A district court may order the decision to be carried out beforehand, even though the decision is denied or appealed. A valid letter is a written letter which according to the applicable regulations for that matter has the strength of evidence, or if there is a previous sentence with a verdict which has obtained definite power, same as if the provisional charges are granted" [11] [14].…”
Section: Law Of Appealmentioning
confidence: 99%